Increasing Junior High School Students’ Awareness of the Importance of Routine Hemoglobin Level Health Examination - Puspa Amalia; Natasya Intan Ramadhani; Nisa Julia Safarti (International Journal Of Health Science, 2025)
Anemia is when a person has fewer red blood cells or lower levels of hemoglobin in their blood than what is normal for their age and gender. In healthy people, red blood cells carry hemoglobin, which helps move oxygen and other nutrients like vitamins and minerals to the brain and body. Normally, males have a hemoglobin level of 13. 5 grams per deciliter, and females have 12 grams per deciliter.This community service was done at SMPN 05 Sungai Kakap and aimed to teach students about the importance of checking hemoglobin levels.The activity used educational talks and hemoglobin testing with a digital device called Easy Touch GCHb.The counseling sessions showed that the students were interested and asked many questions.The hemoglobin test found that out of 24 students tested, 4 girls had levels below 12 g/dl, which means they had anemia.The method used—talks and testing—worked well.The results were then compared with body mass index (BMI), but there was no link between the two. More checks and ongoing care are needed to stop anemia from happening early.